Legislative Bargaining with Reconsideration - Diermeier, D.; Fong, P. (Quarterly Journal of Economics, 2011)
We present a dynamic model of legislative bargaining with an endogenously evolving default policy and a persistent agenda setter. Policy making proceeds until the agenda setter can no longer pass a new policy to replace an approved bill. We prove existence and necessary conditions of pure-strategy stationary equilibria for any finite policy space, any number of players, and any preference profile. In equilibrium, the value of proposal power is limited compared to the case that disallows reconsideration, as voters are induced to protect each other's benefits to maintain their future bargaining positions. The agenda setter, in turn, would prefer to limit his ability to reconsider. The lack of commitment due to the possibility of reconsideration, however, enhances policy efficiency.